(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2025)
Biological traces originating from a human, whether it is a victim or an attacker, or from other persons who happened to be there accidentally or intentionally – are of great importance. These are traces of blood in various quantities and forms, traces of semen, sweat, hair, feces, urine, vomit, meconium. Because they belong to a human, they are called biological traces of human origin, and since they are most often very small quantities, they are called biological micro traces of human origin. The method of collecting, packaging and processing these traces falls within the scope of the work of the police forensic service, and the found material is processed in forensic and forensic laboratories. The aim of this paper is to examine and explain the importance of biological traces in investigative and criminal proceedings, i.e. their use to determine the identity of the person to whom they belong, the relationship between the victim and the attacker during the commission of the crime, the type of participation in a traffic accident, etc. Thanks to these traces, it is possible to find answers to the questions sought by investigative authorities related to a specific case.